Further remarks on a problem of Moser and a conjecture of Mawhin - Andres, Jan (Topological Methods in Nonlinear Analysis, 1995)
Multiplicity results for both periodic and anti-periodic forced oscillations forthe pendulum equation are given on the background of a detailed expositionof the results related to the so-called problem of Moser and to the Mawhinconjecture.